Judicial certainty and creativity: an evaluation of stare decisis - Ismail, Ibrahim (UKM Press, 2004)
Stare decisis forms part of the Malaysian legal system. It is inherited from the English common law. Although the doctrine has its positive aspects such as certainty, stability and continuity but at the same time it also produces some negative elements such as rigidity and in creativity towards the development of a legal system. The main theme of this paper is to examine how far the doctrine of stare decisis has played its role in the society especially in the legal, economic and political contexts. Whether the basis of certainty would deprive the liberty of activism, which was supposed to be played by the judiciary. With the establishment of the Federal Court as the highest court in Malaysia it is hoped that the said court will play its role in order to uphold justice by exercising its judicial power in a judicious manner.